Cultural Convergence: The Isnfluence of Indian Traditions on Birth Traditions in Aceh - Yuni Saputri; Heri Fajri; Widia Munira; Rizka Purnama Sari; Elora Tribedy (ETNOSIA : Jurnal Etnografi Indonesia, 2025)
Studies of Acehnese culture have predominantly focused on Islamic traditions, leaving pre-Islamic heritage particularly the Hindu-Buddhist influence introduced from India largely unexplored. As a central ritual in society marking the beginning of life, birth traditions in Aceh form a cultural genetic system that incorporates Indian, Islamic, and local elements at various level. This study seeks to explore the extent and ratio of Indian cultural influence in Acehnese birth traditions, especially in the context of a society now largely shaped by Islamic values. The study used qualitative ethnographic method based on Spradley’s theoretical framework, with data collected through participant observation and interview. The findings reveal that Indian influence remains evident in the symbols and rituals associated with birth traditions in Aceh, which encompass processions such as Khanduri, Peusijeuk, Intat Bu/Me Bu, Tanom Adoe, and Peutreun Aneuk. More complexly, the Peusijeuk tradition, which involves the use of water and leaves as ritual objects and signifies the aspiration for blessings, is demonstrably a Hindu influence that has since undergone Islamic syncretism, evidenced by the inclusion of Islamic prayers during the ritual. These findings highlight the complex and ongoing nature of cultural assimilation in Aceh, where Indian and Islamic influences coexist within the local cultural framework.